ERROR ANALYSIS OF STUDENTS IN SOLVING THE PISA FINANCIAL LITERACY QUESTIONS - Titik Ulfatun; Tifany Larasati Dewi; Zulfa Izzatun Nikmah; Sengaloun Xaphakdy; Sinabajije Alphonse (Department of Accounting Education, Faculty of Teacher Training and Education Universitas, 2023)
Financial literacy is an important literacy for students. However, there are still many Indonesian students who cannot be completely correct in solving the Programme for Internasional Student Assessment financial literacy questions. The aim of this study is to analyze students’ errors in answering the PISA financial literacy questions. In this qualitative research, the researcher gave financial literacy questions to Grade VIII students of SMP Negeri 189 Jakarta where the questions were at levels 3, 4, and 5. These questions are based on the examples of financial literacy questions issued by the Organisation for Economic Co-operation and Development where these questions can be used as a trial or exercise. Error analysis in solving PISA financial literacy questions used Newman Error Analysis. This research involved 33 students of class VIII SMP Negeri 189 Jakarta. Data collection techniques used test questions, interviews, and documentation. Data analysis techniques included: data managing; reading, memoing; describing, classifying, interpreting; and representing, visualizing. The results of this study indicate that the level of financial literacy knowledge of students at SMP Negeri 189 Jakarta is classified as low. Identification of difficulties found 121 mistakes made by students, 34.7% made mistakes in transformation (42 errors), 27.3% made mistakes in process skill (33 errors), 24.8% made mistakes in comprehension (30 errors), while the rest or around 13.2% made mistakes in encoding (16 errors). Future research is needed to find out what factors influence students' financial literacy.